More than just ticking a box…how patient and public involvement improved the research design and funding application for a project to evaluate a cycling intervention for hip osteoarthritis. Issue 1 (December 2015) - Andrews, Lisa; Allen, Helen; Sheppard, Zoë; Baylis, Guy; Wainwright, Thomas
Plain English summary Involving patients and the public in research helps to ensure that research remains relevant, and has an impact on the people it aims to benefit. Funding bodies now require patients and the public to be involved at all stages of research. Patients and members of the public were involved from the outset in research into a cycling and education programme for hip osteoarthritis. A group discussion took place with six participants from a trial of the programme. The group provided feedback on several areas including the relevance of the research, how the researchers proposed to recruit patients, the research design, the programme itself (including what they liked/didn't like about it), and how the researchers could publicise the research findings. The feedback received was invaluable, and helped shape the entire research project and funding application. The cycling and education programme has been extended in line with comments received from the group. They also helped identify the best way of gathering information from research participants and had suggestions for sharing the results, both of which were incorporated into the funding application. Often involving patients and the public in research can be seen as a 'tick box' exercise. However, this example shows how crucial involving patients and the public in research design is. It also shows how the funding application was made stronger as a result of patient input. Researchers should be encouraged to work closely with patients and the public to ensure their research is of the highest quality. Abstract Background Involving patients and the public in research is an essential activity to ensure relevant, accessible, and appropriate research. There is increasing obligation from funding bodies on researchers to have well thought through plans for involving the public, and indeed it is often a condition for funding. Patient and public involvement activity in this project was conducted to inform a funding application to investigate the effectiveness of a cycling and education intervention in the treatment of hip osteoarthritis. Methods Six participants from a feasibility programme of the intervention attended a two-hour patient and public involvement consultation group to provide feedback on various aspects of the proposed research and intervention. During the consultation group, two independent facilitators followed a detailed plan formulated with the research team. Feedback was validated by the attendees via email following the consultation, and a report was issued to the research team. Further feedback on subsequent changes was sought via email and telephone with members of a Patient Advisory Group. Results The patient and public involvement consultation group provided invaluable feedback and suggestions which impacted on the design and quality of the research project and the intervention. Key changes to the intervention included extending the duration of the cycling programme from six to eight weeks, and inclusion of an exercise diary to promote adherence to the intervention. Key feedback regarding the design of the research and funding application included suggestions for methods of dissemination, and confirmation of the primary outcome measure. Conclusions Patient and public involvement was crucial to the design of the proposed research and intervention. It informed many aspects of the research design and made the funding application stronger as a result. Involving patients and the public in research is much more than an obligation, or 'tick box' exercise. It can change and improve research quality, which is crucial when answering questions that are meaningful and important to patients, and which leads to increased impact. Collaboration with patients and the public should be planned and reported from the conception of a research idea where the impact of such input can be considerable.